Saudi EFL learners’ use of English Modal Verbs: A study of challenges and solutions - Ahmed, Mahdi Aben (International Journal of Language and Literary Studies, 2021)
It has been reported that English modal verbs can be one of the most difficult grammatical structures to be mastered by EFL learners. Hence, this research aims to explore the reasons behind Saudi EFL students’ low proficiency level in using English modal verbs. It also seeks practical solutions for enhancing the students’ competency in using them. The study participants are 13 Saudi EFL instructors who are requested to answer an open-ended descriptive question. These responses are then coded thematically to identify the recurring themes. Findings of the study show that the most prominent reasons for students’ poor performance in the use of modal verbs are: (i) absence of Arabic equivalents to English modals; (ii) difficulty of English structures; (iii) multiple language functions of English modals; (iv) demotivation of students; (v) use of traditional textbooks and teaching pedagogy. Moreover, the study shows that to increase the Saudi EFL learners’ proficiency in the use of English modals, (i) EFL instructors need to use communicative teaching methodology; (ii) urge students for more practice and; (iii) use suitable textbooks and teaching resources. The study recommends inclusion of the grammar component according to the students’ existing knowledge and explicit teaching.